Numerical analysis of the effect of torispherical head on the buckling of pressure vessel - KHOSHRAVAN, M. R.; RAHMANI, A. (Engineering Transactions, 2009)
The shape of end heads of a pressure vessel is usually torispherical. Buckling of this head is one of the most important points for designing of pressure vessels. This subject has been studied extensively since last years. In this field, the experimental methods are expensive and need a lot of time. In addition, because of lack of accuracy in the producing procedure, sometimes two models with identical geometry show different buckling behavior. Hence the use of finite element method in analyzing of buckling behavior of heads has a lot of benefits. In this dissertation, the finite element method has been used. Firstly with nonlinear buckling analysis, the effects of geometrical parameters such as thickness, knuckle radius and diameter of cylindrical part, on the buckling of heads have been studied, then the buckling behavior of different kinds of heads with identical geometry have been analyzed. For the nonlinear analysis we used the Arc Length method which can control the load level, the length of the displacement increment and the maximum displacement. The most important characteristic of this method is its ability to converge, even when the behavior is highly nonlinear. From the verification performed with the European Convention for Constructional Steelwork (ECCS) code, it has been confirmed that the nonlinear buckling analysis could assure accurate results for the buckling strength. In the case of internal pressure, it has been shown that initial imperfection had no effect on the pre-buckling behavior and buckling pressure of head; it just affects the post-buckling behavior.